1992
DOI: 10.1091/mbc.3.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization of full-length heparin-binding growth associated molecule.

Abstract: Heparin-binding growth-associated molecule (HB-GAM) was purified from adult bovine brain and chicken heart. The yield of HB-GAM is increased by 5- to 10-fold when 250 mM NaCl is added to the homogenization buffer, indicating that HB-GAM may exist as a complex with an insoluble component of the tissue. The complete amino acid sequence of the brain-derived HB-GAM was established by automated Edman degradation of the intact protein and chemically or enzymatically derived fragments. The mass of bovine HB-GAM as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
0
27

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 25 publications
2
56
0
27
Order By: Relevance
“…Its reactivation in adults strongly promotes angiogenesis and vascular growth in tumors (4, 8 -10), and it has served as a marker of cancer erosion, angiogenesis, and metastasis (11,12). In ectodermal derivatives, it promotes neurite outgrowth (13) and glial cell differentiation (5). Following acute ischemic injury to brain, it is up-regulated (14), and it enhances neuron survival (15).…”
mentioning
confidence: 99%
“…Its reactivation in adults strongly promotes angiogenesis and vascular growth in tumors (4, 8 -10), and it has served as a marker of cancer erosion, angiogenesis, and metastasis (11,12). In ectodermal derivatives, it promotes neurite outgrowth (13) and glial cell differentiation (5). Following acute ischemic injury to brain, it is up-regulated (14), and it enhances neuron survival (15).…”
mentioning
confidence: 99%
“…Pleiotrophin is a very basic protein of an apparent mass of 18 kDa, which is differentially expressed during preand postnatal development (Hampton et al, 1992). During embryogenesis PTN is strongly expressed in brain, liver, spleen, lung, bone and tongue.…”
mentioning
confidence: 99%
“…After interaction with their specific receptors, these hormones induce the synthesis of regulatory peptides that either positively or negatively control the homeostatic maintenance of the mammary gland. Using in vitro as well as in vivo experiments, various regulatory peptides have been identified and implicated in breast tissue growth, including transforming growth factors ␣ and ␤ , epidermal growth factor, insulin-like growth factors I and II, platelet-derived growth factors A and B, vascular endothelial growth factor, fibroblast growth factors (for review see Dickson and Lippman 1995) and, more recently, pleiotrophin (PTN) (Garver et al 1994) also called heparin affin regulatory peptide (HARP) (Courty et al 1991), heparin-binding growth-associated molecule (HB-GAM) (Hampton et al 1992), or heparinbinding neurotrophic factor (HBNF) (Kovesdi et al 1990). This heparin-binding molecule is an 18-kD molecule that plays a role in cell growth and differentiation (for review see Laaroubi et al 1995).…”
mentioning
confidence: 99%
“…This polypeptide is a member of a new family of heparin-binding growth factors including the midkine (MK) (Kadomatsu et al 1988) and its chicken homologue, called retinoic acid-induced heparin binding (RI-HB) factor (Raulais et al 1991). Initially isolated from neonatal rat brain as a molecule that induced neurite outgrowth of embryonic neurons (Rauvala 1989), this polypeptide was also shown to be present in non-neuronal tissues, including heart (Hampton et al 1992), uterus (Milner et al 1989), cartilage (Neame et al 1993), and bone (Zhou et al 1992) extracts. In addition to its role during neuronal development, several studies have shown that HARP was able to induce the proliferation of epithelial, fibroblast, and endothelial cells (Li et al 1990;Courty et al 1991;Fang et al 1992) and to stimulate in vitro the characteristic processes of angiogenesis (Laaroubi et al 1994).…”
mentioning
confidence: 99%